Brand logo and brand gender: examining the effects of natural logo designs and color on brand gender perceptions and affect - Machado, Joana César (2021)
This paper examines how a critical dimension of logo design, namely naturalness, along with logo color, influences brand gender perceptions, and whether brand-design-induced gender perceptions ultimately impact affective reactions to logos. Data were collected from a sample of 260 participants, using a set of 24 unknown, manipulated logos as stimuli. Results suggest that while cultural logo designs effectively convey brand masculinity, organic logo designs enhance femininity perceptions. Using dark blue and light pink logo colors reinforce masculinity and femininity perceptions, respectively. Both logo masculinity and logo femininity have a positive effect on the affective response toward logos. Furthermore, this research analyzed the moderation effect of color on the link between logo design and logo gender perceptions, as well as the moderation effect of consumers’ gender in the link between logo gender perceptions and affect toward the logo. However, none of these moderation effects were supported by the data. This is the first research to empirically test the effect of natural logo designs on brand gender perceptions and, thereby, on affective reactions toward the logo. The findings provide practical guidelines about the design of a gendered logo using the naturalness of logo design and logo color, thereby facilitating gender targeting efforts